Response of the copepod community to interannual differences in sea-ice cover and water masses in the northern Barents Sea - Gawinski, Christine; Daase, Malin; Primicerio, Raul; Amargant-Arumí, Martí; Müller, Oliver; Wold, Anette; Ormańczyk, Mateusz Roman; Kwasniewski, Slawomir; Svensen, Camilla (Frontiers in Marine Science, 2024)
The reduction of Arctic summer sea ice due to climate change can lead to increased primary production in parts of the Barents Sea if sufficient nutrients are available. Changes in the timing and magnitude of primary production may have cascading consequences for the zooplankton community and ultimately for higher trophic levels. In Arctic food webs, both small and large copepods are commonly present, but may have different life history strategies and hence different responses to environmental change. We investigated how contrasting summer sea-ice cover and water masses in the northern Barents Sea influenced the copepod community composition and secondary production of small and large copepods along a transect from 76°N to 83°N in August 2018 and August 2019. Bulk abundance, biomass, and secondary production of the total copepod community did not differ significantly between the two years. There were however significant spatial differences in the copepod community composition and production, with declining copepod abundance from Atlantic to Arctic waters and the highest copepod biomass and production on the Barents Sea shelf. The boreal Calanus finmarchicus showed higher abundance, biomass, and secondary production in the year with less sea-ice cover and at locations with a clear Atlantic water signal. Significant differences in the copepod community between areas in the two years could be attributed to interannual differences in sea-ice cover and Atlantic water inflow. Small copepods contributed more to secondary production in areas with no or little sea ice and their production was positively correlated to water temperature and ciliate abundance. Large copepods contributed more to secondary production in areas with extensive sea ice and their production was positively correlated with chlorophyll a concentration. Our results show how pelagic communities might function in a future ice-free Barents Sea, in which the main component of the communities are smaller-sized copepod species (including smaller-sized Calanus and small copepods), and the secondary production they generate is available in energetically less resource-rich portions.